2001
DOI: 10.1046/j.1523-1755.2001.059002498.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-transforming growth factor-βbgr; antibodies in cyclosporine-induced renal dysfunction

Abstract: In this rat model of CsA-induced nephrotoxicity, renal insufficiency and characteristic histologic changes are associated with altered expression of matrix and matrix-regulating molecules. Based on our results with alpha-TGF-beta antibodies, many but not all of these nephrotoxic effects of CsA are mediated by TGF-beta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 24 publications
6
80
0
Order By: Relevance
“…35 A number of studies have implicated TGF-␤ as a key mediator of cyclosporine-induced nephrotoxicity, but definitive evidence has only recently been reported. Our laboratory 15 and those of others 36,37 have examined the effects of administering TGF-␤-neutralizing antibodies to nontransplantation models of cyclosporine nephrotoxicity. These studies have shown that blocking TGF-␤ can normalize the expression of collagen types III and I and substantially reduce overall tissue fibrosis when examined histologically.…”
Section: Discussionmentioning
confidence: 99%
“…35 A number of studies have implicated TGF-␤ as a key mediator of cyclosporine-induced nephrotoxicity, but definitive evidence has only recently been reported. Our laboratory 15 and those of others 36,37 have examined the effects of administering TGF-␤-neutralizing antibodies to nontransplantation models of cyclosporine nephrotoxicity. These studies have shown that blocking TGF-␤ can normalize the expression of collagen types III and I and substantially reduce overall tissue fibrosis when examined histologically.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A stimulates levels of circulating TGF-␤ in vivo (Khanna et al, 1997), and enhances TGF-␤ production by renal cells and lymphocytes (Ahuja et al, 1995;Prashar et al, 1995;Young et al, 1995;Wolf et al, 1996). This results in increased collagenous extracellular matrix synthesis and deposition in the glomeruli of the kidney, as demonstrated by studies with anti-TGF-␤1 antibodies that block renal fibrosis and renal dysfunction (Shihab et al, 1996;Islam et al, 2001). Taken together, these studies suggest that cyclosporin A stimulates TGF-␤ production that, in turn, leads to kidney fibrosis and nephropathy.…”
Section: Unique Aspects Of Gingival Fibroblast Metabolismmentioning
confidence: 91%
“…One potential mechanism for upregulation of matrix appears to be via the pleotropic cytokine TGFβ. Not only is TGFβ production increased along with matrix proteins in cultured cells after calcineurin inhibition [4], but CsA-mediated fibrosis can be reduced by neutralizing TGFβ antibody in vivo [5,6]. From these experiments, it is reasonable to conclude that calcineurin activity negatively regulates TGFβ and, consequently, extracellular matrix.…”
Section: Introductionmentioning
confidence: 90%